ESP Needs Analysis Based Syllabus of Economics Faculty Students, Universitas “45” Makassar - Lalu Abdul Khalik (Bandar Lampung University (UBL), 2014)
The main objective of this research is to design a syllabus and adapt materials on the basis of Students’ needs. In order to achieve this objective, needs analysis of the students was carried out in advance. The research was conducted in Makassar by employing pre-ESP and post-ESP students as the source of primary data. As The source of supporting data, the researcher distributed questionnaire to graduates, ESP teachers, Head of Departments and graduates’ employers/users. To effectively achieve the objective of the research, the researcher conducted a survey by distributing questionnaire and document study to collect relevant data. The data which had been collected were then tabulated and analyzed by using descriptive method. The results of the research indicate that conducting needs analysis prior to any ESP course is absolutely important as the basis for syllabus design and material adaptation, because there was no material available on the market that could fully fit the students’ needs. The results of the target situation analysis also indicates that the main purpose of the students of Economic Faculty , Universitas “45” Makassar in learning ESP is to enable them to read and understand books related to economics written in English that are available in libraries. Based on this fact the researcher tried to design a syllabus that integrated reading skills, vocabulary acquisition and mastery on English grammar. Further, the materials were arranged based on the students’ topic of interest/priority.